Impact of Demonetization on the Indian Economy - SHYAM SUNDAR KAPRI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Demonetization is the procedure for eliminating a monetary unit's legal tender status. In an effort to combat black money, corruption, and counterfeit money, the Indian government executed demonetization by banning the 500 and 1,000-rupee notes in November 2016. The decision provoked mixed responses, with some applauding the government's audacity and others criticizing it for seriously disrupting the economy. The impacts of demonetization on the Indian economy, including their implications on GDP, inflation, employment, and other economic indices, are thoroughly looked at in this paper. Demonetization impacted the Indian economy in the near term, the research finds, but its long-term repercussions are yet unknown but they can be assumed. (Veerakumar, 2017) This study uses data from 2015 to 2017 to provide a longitudinal analysis of the effects of demonetization on the Indian economy. Statistical techniques including regression analysis, t-tests, and time-series breakdown are used in the analysis. This paper will also discuss reviews of different individuals on demonetization as well as the people who were arrested during this time period.